Dampak Investment Opportunity Set, Komite Audit, dan Audit Tenure terhadap Audit Report Lag: Sebuah Analisis Empiris - Rohim, Abi; Annisa, Dea (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to examine the influence of investment opportunity set, audit committee and audit tenure on audit report lag in basic materials sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020 – 2022 period. This research uses a quantitative approach and uses associative methods. The type of data used in this research is secondary data. The panel data regression method was used as the research methodology in this study. Analysis of research results using E-Views 12 and Microsoft Excel software. The population used in this research is basic materials sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020 – 2022 period. The sample used in this research was 60 companies in the basic materials sector during the 2020 – 2022 period. The research results show that simultaneously investment opportunity set, audit committee and audit tenure influence audit report lag. Partially, the investment opportunity set variable has an effect on audit report lag, while the audit committee and audit tenure variables have no effect on audit report lag.